TECHNOLOGY FOR GROWING CHILDREN'S SPEECH THROUGH PLAY SESSIONS (Eureka Journal of Language, Culture & Social Change, 2026)
This article covers the pedagogical, psychological and methodological significance of educational games in the process of developing children's speech in preschool educational institutions. The role of educational games in the cultivation of children's speech, their impact on mental, moral and Social Development, has been scientifically-theoretically analyzed. The article reveals on the basis of examples the content, tasks and methodology of their organization of educational games intended for different age groups. It is also based on the importance in the development of speech of planning, repetition of training, an individual approach, the creation of an emotional environment and the observance of the principles of exhibitionism. The results of the study show that educational games are an effective tool for enriching children's vocabulary, increasing speech activity and forming independent thinking skills.
Keywords: Speech, oral speech, educational game, vocabulary enrichment, speech activity, mental development, educator activity, mind